The Gondwanan Green Alga Tasmanites sp. in the Permian Lacustrine Deposits of West Timor - Eko Budi Lelono (Geological Agency, 2019)
DOI: 10.17014/ijog.6.3.255-266This paper discusses a palynological research on the Permian lacustrine sediments of West Timor. Ten outcrop samples were collected from a 5 m high cliff. Lithologically, the outcrop mostly consists of noncalcareous black shale showing papery structures and forms part of Bisane Formation. Palynomorphs extracted from the studied samples are rich, but of a low diversity indicating a non-marine environment. More than 80% of pollen assemblages are of the green alga Tasmanites sp., whilst the rest are mostly represented by striate and non-striate bisaccate pollen and trilete spores which indicate a Permian age. The chromatograms of GC and GCMS (saturate) indicate that the studied samples were deposited in a lacustrine environment of an anoxic to suboxic condition. Furthermore, in term of petroleum exploration, abundant Tasmanites sp. is believed to be the biological source for tricyclic terpanes which are well known as the primary source of hydrocarbons. This discovery offers an excellent opportunity for establishing a new petroleum system within the Paleozoic sequences of Timor Island.